HomeIssuesEditorial BoardPoliciesDocuments & LinksUoSContact علاقة بعض القدرات الحركية بأداء أنواع التصويب للاعبي منتخبات التربية بكرة السلة بأعمار 16-17 سنة - الفرطوسي, علي سموم; عباس, نصير خضير (Sulaimani Journal for Humanities, 2018)
The main objective of the attack in the game of basketball Accuracy is necessary each trying to throw the ball toward the basket .It is important to study what the capabilities of the kinetic parameter affects the performance of the basic skills of scoring in the game of basketball, whether stability or movement .The research's problem lies in the weakness of the cognitive side and the lack of understanding of each skill correction through the motor. The aims of the research (Identify the most important motor special abilities and skills of the shooting in the game of basketball, Knowledge of the relationship between the motor variables and among the surveyed correction variables in the game of basketball, using the canonical correlation). The researcher used descriptive method in the survey style and relations of mutual connectivity. The sample of the study were (80) players. A section views the results analysis of the variable under study and which has been reached to achieve the objectives of the reseal. It includes Conclusions and recommendations. There is a significant relation between (motor abilities) and (skills, variables) as a whole .The independent variables passed in explaining (10.7321) percentage of the total variation in the skills, variables.